Perilaku Kepatuhan Masyarakat dalam Menerapkan Protokol Kesehatan Covid-19 - Alfiyah, Fifi; Santik, Yunita Dyah Puspita (Indonesian Journal of Public Health and Nutrition, 2023)
Background: The Covid-19 pandemic in Indonesia is a health problem that has not yet ended. Covid-19 cases in Indonesia on 31 May 2022 were 6.054.973 cases. Indonesia ministry of Health informed that SARS-CoV-2 continues to mutate to form new variants. Therefore, efforts are needed to prevent the transmission of Covid-19 through the implementation of the Covid-19 health protocol. The purpose of this studi was to determine the factors related to community adherence in implementing the Covid-19 health protocol in the Karangsari Healthcare Center, Cirebon Regency. Method: This type of research uses an analytical survey with a cross sectional design. The research sampel is 99 respondents, with cluster sampling technique. The instrument used a questionnaire. Data were analyzed by chi square test and logostic regression. Results: The result show that knowledge (P=0,009, RP=1,470) and attitude (P=0,003, RP=1,564) are related to community adherence in implementing the Covid-19 health protocol in the Karangsari Healthcare Center, Cirebon Regency. Conclusion: There is a significant related between knowledge and attitude with adherence in implementing the Covid-19 health protocol. Attitude is the factors that most influence the adherence in implementing the Covid-19 health protocol in the Karangsari Healthcare Center, Cirebon Regency.